2014
DOI: 10.1002/jbmr.2383
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia and Fractures: Findings From the MrOS Study

Abstract: Hyponatremia may be a risk factor for fracture. To determine the relationship between hyponatremia and fracture we conducted cross-sectional and longitudinal analyses using data from the Osteoporotic Fractures in Men Study (MrOS). The MrOS study enrolled 5122 community dwelling men aged ≥ 65 years from six centers across the United States. We excluded men taking bisphosphonates, those with unknown medication history, those without serum sodium measures, or those with out of range assays for serum sodium. Serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 21 publications
3
44
0
Order By: Relevance
“…Most recently, Jamal et al (26) studied the association of hyponatremia with fractures among 5122 elderly communitydwelling men using data from the Osteoporotic Fractures in Men Study. Baseline prevalence of hyponatremia was 1.25%.…”
Section: Mild Chronic Hyponatremia and Risk Of Morbiditymentioning
confidence: 99%
“…Most recently, Jamal et al (26) studied the association of hyponatremia with fractures among 5122 elderly communitydwelling men using data from the Osteoporotic Fractures in Men Study. Baseline prevalence of hyponatremia was 1.25%.…”
Section: Mild Chronic Hyponatremia and Risk Of Morbiditymentioning
confidence: 99%
“…Hence, the likelihood of hyponatremia to lead to fractures through other effects on bone such as decreased bone quality, which is not captured by BMD, has also been emphasized (8). In a longitudinal analysis of data from the Osteoporotic Fractures in Men Study (MrOS), it was reported that after adjusting for age, BMI, study center, and other covariates, hyponatremia was associated with up to a doubling in the risk of hip and morphometric spine fractures, independent of BMD (25). Accordingly, aside from reduction in BMD, chronic hyponatremia has also been associated with increased fracture rates in elderly (4,8,11,(14)(15)(16) and with metabolic bone loss through an uncoupling of bone resorption and formation in rats indicating the effect of hyponatremia on bone quality (10).…”
Section: Discussionmentioning
confidence: 99%
“…First, the study utilizes ePASP as a proxy for invasive hemodynamic measures. While echocardiography provides a reliable estimate of ePASP, 8 its utility as a tool for…”
Section: Disclosuresmentioning
confidence: 99%
“…Furthermore, in population-based studies, chronic hyponatremia associates with bone fracture risk [6][7][8] ; however, whether this is a consequence of a neurologic phenotype predisposing to falls 9 or of a bone phenotype predisposing to fracture 10 (or perhaps a combination of both) remains unclear.…”
mentioning
confidence: 99%